2019
DOI: 10.1111/cid.12758
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and factors determining new bone formation in lateral sinus membrane elevation with simultaneous implant placement without grafting material: A cross‐sectional, 3‐17 year follow‐up study

Abstract: Background Lateral sinus membrane elevation with simultaneous implant placement without grafting material (graft‐less LSFE) is a widely investigated method for bone augmentation of the maxillary sinus floor. Long‐term follow‐up studies are rare. Purpose This study aimed to investigate the long‐term effects of implants placed with graft‐less LSFE. Materials and methods The study group was comprised of 111 patients previously treated with graft‐less LSFE. The first follow‐up visit, which occurred after a mean of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
5
11
0
Order By: Relevance
“…Maxillary sinus membrane elevation (MSME) applying the lateral window technique without a grafting material and simultaneous implant placement has demonstrated high survival rates of suprastructures and implants, intrasinus bone regeneration, and limited peri‐implant marginal bone loss, as documented in systematic reviews (Moraschini et al, 2017; Silva et al, 2016; Starch‐Jensen & Schou, 2017). These results are in accordance with a newly published long‐term study revealing an overall implant survival of 95.9% and intrasinus bone gain of 4.0 mm after MSME and blood coagulum (Lundgren et al, 2019). Short‐term studies have reported successful implant treatment outcome and high patient satisfaction with the prosthetic rehabilitation after MSME and blood coagulum compared with MSFA using different grafting materials (Altintas et al, 2013; Borges et al, 2011; Lie et al, 2015).…”
Section: Introductionsupporting
confidence: 91%
“…Maxillary sinus membrane elevation (MSME) applying the lateral window technique without a grafting material and simultaneous implant placement has demonstrated high survival rates of suprastructures and implants, intrasinus bone regeneration, and limited peri‐implant marginal bone loss, as documented in systematic reviews (Moraschini et al, 2017; Silva et al, 2016; Starch‐Jensen & Schou, 2017). These results are in accordance with a newly published long‐term study revealing an overall implant survival of 95.9% and intrasinus bone gain of 4.0 mm after MSME and blood coagulum (Lundgren et al, 2019). Short‐term studies have reported successful implant treatment outcome and high patient satisfaction with the prosthetic rehabilitation after MSME and blood coagulum compared with MSFA using different grafting materials (Altintas et al, 2013; Borges et al, 2011; Lie et al, 2015).…”
Section: Introductionsupporting
confidence: 91%
“…A recent study on RABH ranging from 2 to 8 mm below the maxillary sinus reported that the sinus elevation technique without employing grafting material worked independently of the thickness of the residual alveolar bone, with overall 95.9% implant survival after 8 years [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…These assessments require histological analyses that always involve some additional biological cost. Similarly, the length of the implant protruding into the sinus cavity under the elevated membrane is a strong factor influencing the success of the procedure [ 43 ]; however, the implant length/RABH ratio was not taken into account in our follow-up. In this respect, it should be noted that the length of the implant itself might not be a relevant factor in the biological prognosis of the treatment, as shorter dental implants as well as longer dental implants in conjunction with lateral sinus elevation procedures yielded similar marginal bone level changes [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…e use of graft material is reported in most of the works with the aim of acting as a shock absorber during the osteotomy procedure but mainly inducing bone formation around the implant. However, various studies consider the mere blood clot as an effective generator of new bone [7][8][9][10][11]. In 1993, Boyne achieved bone regeneration under the sinus mucosa in an animal model without the use of filler material but by lifting the mucosa and at the same time inserting the implants, with the sole purpose of creating the so-called "curtain effect" [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the use of blood clot alone seems as effective as the use of filling materials with both lateral and crestal approaches. In both surgical techniques, a space is created between the membrane and the floor of the maxillary sinus which is initially filled by the blood clot, and subsequently new bone is formed, following the principle of “GBR” (guided bone regeneration) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%